Crop diversification through maize-based cropping systems - Kumar, Ashok; Singh, Ishwar (Indian Farming, 2015)
Crop diversification in maize through maize-based croppingsystems is beneficial in improving the productivity and profitability with efficient utilization of inputs. The diversification is possible under both sequential and intercropping systems by including different type of maize and maize hybrids.